Causals of Time-Scaled Volatility, Business Cycles and Macro-Economic Indicators: A Wavelet Analysis of Selected Islamic Countries - Gulzar, Muhammad; Kalim, Rukhsana (International Journal of Contemporary Economics and Administrative Sciences, 2021)
The inconsistent nature of the RBC makes necessary to understand the relationship between stock performance and economic activity. This study attempts to establish the relationship between ISI with selected macroeconomic indicators and RBC. By using 12 years’ monthly data the results has extracted after using ARCH/GARCH, wavelet analysis with MOWDT Daubechies filter of at scale 3 of symmlet 8 as well as panel ARDL for three Islamic countries. The findings confirms that ISI appears to be less volatile in expansion phase of RBC and high during recession but decreases gradually as the time scale expands . Moreover, TO, OP, CPI and BD have also significant relationship with ISI. Countrywide analysis showed that Islamic stock markets of selected countries are receptive to shrinkage and expansion of economic activities. The outcome of the study brings insight that how shock in ISI stability may affect future output and ISI is a useful variable of economic stability